Family and School Integration in the Development of the Creativity Component in Students Based on Collaboration Technology (Journal of Pedagogical Inventions and Practices, 2023)
this article talks about the fact that cooperation technology is an activity aimed at making certain changes in the practice of educational institutions to develop the creativity component in students.